Pertumbuhan dan Kandungan Agar Rumput Laut (Gracilaria spp) Pada Beberapa Tingkat Salinitas - Anton Anton (Jurnal Airaha, 2017)
The aims of this study was to know the salinity level which perform highest growth rate and agar contents on the Gracilaria spp in the homogen cultivation condition. This research was carried out in the Laboratory of SUPM Bone, and the Laboratory of faculty marine and fisheries science, Hasanuddin University, from July until October 2004. Fifteen peaces of wooden tanks with size 1 x 1 x 0.45 meters were used as experimental basins. Each basin contained sea water with 40 cm height. Gracilaria verrucosa, G. lichenoides, and G. gigas taken from the fishpond around the experimental location were used as experimental plants. Every basin was planted with 100 grams of seaweed using bottom method. The experimental design used was Randomised Block Design (RBD) with five salinity treatments, namely 10, 15, 20, 25, and 30 ‰. The results of this study showed that salinity of 20 ‰ (S3) and 25 ‰ (S4) gave highest daily growth rate, that was 2.40% and the highest agar contents (40.71%) was obtained at the salinity of 20 ‰ (S3).The daily growth rate of 10 permil (S1) salinity treatment reached its peak at week III, while the salinity treatment of 15 ‰ (S2), 20 ‰ (S3) salinity, 25 ‰ salinity (S4), and 30 ‰ salinity (S5) reached its peak in week IV.